COMMUNICATIVE COMPETENCE IN FOREIGN LANGUAGE TEACHING (International journal of artificial intelligence, 2025)
The article considers general tendencies in world and national education, and also both principles and methods of forming professional, communicative, intercultural competences and in the process of teaching foreign language for professional purposes in the conditions of engineering, economic and other non-linguistic specialties at technical university. The article views some essential issues of this competence including awareness of pedagogical values, the construction of the pedagogical process, pedagogical communication ; pedagogical technology, its essence, structural components, requirements for the design and engineering of pedagogical technologies.